Pengaruh Positive Reinforcement terhadap Hasil Belajar Sejarah Siswa di SMA Adiguna Bandar Lampung - Kurniawan, Putut Wisnu (Lentera: Jurnal Ilmiah Kependidikan, 2018)
The main problem in the history learning process seen in grade X students of Adiguna High School Bandar Lampung shows that the learning strategy used has not improved the students learning motivation. The purpose of this study is to determine the influence of positive reinforcement on the learning outcomes of Adiguna high school students in Bandar Lampung lesson year 2017/2018. In the implementation of this study the authors use experimental methods, with a sample of 37. Sampling technique in this study using cluster random sampling technique, data collection techniques using the test. To test the hypothesis, the authors in this study using the formula ttes. From the research results obtained thit value = 4.45> ttab = 2,00 means it can be concluded "There is influence Positive Reinforcement on the learning outcomes of students of class X SMA Adiguna Bandar Lampung Lesson 2017/2018". The average of learning outcomes in the experimental class is 76.64, while the mean of the learning achievement in the control class is 67.21, it can be concluded from the research result that is the average of the students learning outcomes in the learning of applying positive reinforcement higher than the average. average learning outcomes of students in learning apply negative reinforcement.